Female-biased effects of aging on a chimeric hemagglutinin stalk-based universal influenza virus vaccine in mice. Issue 11 (8th March 2022) - Dhakal, Santosh; Deshpande, Sharvari; McMahon, Meagan; Strohmeier, Shirin; Krammer, Florian; Klein, Sabra L.
Highlights: Antibody responses and protection to a cHA-based universal influenza virus vaccine declines with advanced age. Age-associated decline in antibody responses and protection is more prominent in females than males. Serum from vaccinated adult mice is not sufficient to protect naïve aged, sex-matched mice. Age and sex should be considered in preclinical and clinical studies with universal influenza virus vaccines. Abstract: To determine if biological sex and age intersect to affect universal influenza vaccine-induced immunity, adult and aged male and female C57BL/6 mice were sequentially immunized with a chimeric-hemagglutinin (cHA) stalk-based H1 vaccine. Adult mice developed greater quantity and quality of H1-stalk antibodies, that were more cross-reactive with other group 1, but not group 2, influenza viruses, than aged mice. The vaccine did not induce neutralizing or hemagglutination inhibition antibodies, but rather antibody-dependent cellular cytotoxicity, which was greater in adult than aged mice. Vaccinated adult mice were better protected than aged mice after challenge with 2009 H1N1 virus, experiencing less morbidity and having lower pulmonary virus titers. The age-associated decline in immunity and protection was consistently greater among females than males, with the reduction in immunity and protection for aged as compared with adult females often being the sole comparison driving the overall age-associated significant differences. The age-associated reduction in stalk-based immunity in females was not, however, associated with changes in estradiol. To determine if the better antibodies in adults could be utilized to protect aged mice, serum was passively transferred from vaccinated adult mice into naïve sex-matched aged mice. Even with transferred serum from young adult mice, aged females still suffered greater morbidity than aged males. These data suggest there are sex-dependent effects of aging on cHA-based universal influenza virus vaccine-induced immunity that cannot be reversed through transfer of serum from young animals. The lack of consideration of sex-specific effects of aging on immunity could hinder efforts toward universal vaccines.